2011
DOI: 10.2174/1875318301104010015
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Separate Isolation of Cell-Free DNA and Cellular DNA from Urine-Application of Methylation-Specific PCR on both DNA Fractions

Abstract: Abstract:The analysis of genomic DNA is widely-used for research, forensic and diagnostic purposes. Here we describe reliable methods for isolation of cell-free DNA and cellular DNA from urine. Both DNA fractions are suitable for PCR and Methylation-Specific PCR (MSP) amplification, leading to consistent and reproducible results. A kinetics analysis describes the decline of efficiency of MSP performed with urinary DNA which had been stored at room temperature with and without proteinase K for various time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…DNA present in urine can either be cell free, or it can originate from intact cells. Cell-free DNA is derived from apoptotic or necrotic cells, which were thought to mainly originate from the urothelial tract, while exfoliated tumor cells, uro epithelial cells and leukocytes make up the portion of DNA derived from intact cells shed into the urine [12]. However, cell-free nucleic acids have been found to pass through the glomerular membrane in the kidneys, making their way into the urine [13].…”
Section: Preliminary Communicationmentioning
confidence: 99%
“…DNA present in urine can either be cell free, or it can originate from intact cells. Cell-free DNA is derived from apoptotic or necrotic cells, which were thought to mainly originate from the urothelial tract, while exfoliated tumor cells, uro epithelial cells and leukocytes make up the portion of DNA derived from intact cells shed into the urine [12]. However, cell-free nucleic acids have been found to pass through the glomerular membrane in the kidneys, making their way into the urine [13].…”
Section: Preliminary Communicationmentioning
confidence: 99%
“…Recently, we have shown that cell-free DNA can be routinely isolated from urine and used in a Methylation Specific PCR (MSPCR) approach [29]. Here we present further progress and demonstrate that this highly interesting DNA fraction is unrestrictedly amenable by bisulfite genomic sequencing and global, array based DNA methylation analyses.…”
Section: Introductionmentioning
confidence: 83%
“…The converted DNA served as template for amplification of methylated LINE-1 sequences in a normalized real time MSPCR approach as reported by Beermann et al [29].…”
Section: Real Time Methylation Specific Pcr Of Differentially Methylamentioning
confidence: 99%